TOTAL SUSPENDED PARTICULATES FROM CRUDE OIL SPILL - OYETUNJI BABATUNDE OKEDERE; ADEWOLE JOHNSON ADESANMI; JACOB ADEMOLA SONIBARE; OLUSOLA ADEDAYO ADESINA; GBADEBO OMONIYI ADENIYI (Journal of Engineering Studies and Research)
Total suspended particulates emitted during crude oil spill were investigated using laboratory simulation experiments. This was with a view to establishing the toxicity potentials of emitted particulates. Climatic and spill media conditions similar to those obtainable in real life were created in an environmental chamber and the total particulates emitted during spills involving three crude oil samples of Nigerian origin were measured with Quick Take sampler. The toxicity potentials of the emitted particulates were subsequently determined by dividing the 24- hour averaging period concentrations of the particulates by the statutory limit. The statutory limits used were those of Nigeria’s Federal Ministry of Environment (FMENV), World Bank and the World Health Organization (WHO). For temperatures between 15 ºC and 35 ºC and spill media (over fresh water, sea water and soil), the extrapolated 24 – hour averaging period concentrations ranged between 186.79 – 584.28 μgm-3, 186.98 - 584.48 μgm-3 and 247.40- 350.21 μgm-3 for sample A; 183.44 – 571.99 μgm-3, 183.63 -572.19 μgm-3 and 244.05-337.92 μgm-3 for sample B and 178.41 – 566.96 μgm-3, 178.61 - 567.16 μgm-3 and 332.89- 280.60 μgm-3 for sample C. The observed TSP concentrations breached the WHO (lower limit) and World Bank limits at all temperatures and over all spill media and consequently the toxicity potentials exceeded 1.0 which were indications of hazards to human health. The study concluded that particulate emissions during crude oil could be high enough to pose threats and suggested adequate protection for cleaning up workers.